Design and Expert Validation of an Inquiry Based Instructional Design for Basic Physics Laboratories Integrated with Local Context - Ariani, Tri; Maison, Maison; Purwaningsih, Sri; Hariyadi, Bambang (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to design and validate an inquiry based instructional design for Basic Physics laboratories integrated with local context at the higher education level. The research employed a Research and Development (R&D) approach using the ADDIE model, limited to the stages of analysis, design, development, and expert validation. The developed products consisted of a student laboratory manual and a lecturer guide structured into pre-laboratory, in-laboratory, and post-laboratory inquiry phases, with local context positioned as a source of authentic physical phenomena and problem situations. Expert validation was conducted by instructional design experts, physics content experts, and learning media experts using a Likert scale based validation instrument analyzed with Aiken’s V coefficient. The validation results indicate that the instructional design demonstrates a high level of validity and feasibility across conceptual, material, and media aspects, confirming its suitability for use in Basic Physics laboratory learning. This study contributes a systematically validated instructional design framework for inquiry based physics laboratories that integrates local context as a core component of laboratory activities, providing a theoretically grounded and practically feasible design for future implementation and effectiveness studies